Happy city: City discussions - Sağdıç, Zafer; Aydın, Aysun (Sakarya University, 2015)
City, to where the citizen belongs to as being the citizen, thus having an identity with the city, to live in the city, with or without the rights of the citizenship. Well, on which point will the citizen be right- while living inside the city/ while trying to live on the city-? If being happy/ living happy is the will of each and every of us, who is going to create this happiness to us? we? or the others? who else? the country? the government? or the authorities? or the capitalism that we live for? or it’s new face , the neo-liberalist economies? Well, where is the citizen undercover on the city? till where is the citizen right inside the city? Every city user has a dream, an illusion, an imagination not only related with the city, but also about living on that city; and if the citizen has a utopia, then whose dystopia would it be. In other words whose utopia can be who else’s dystopia? Or whose utopia is a dream as having a mythical origin in the city where he lives? Searching, discussing, rejecting the “happy city “ are just some words of the lullabies of our childhood days? Or can those concepts be the basic points of our daily life? Each and every citizen has a dream in the city, being happy on the city by living the dreams or rejecting the city after seeing a nightmare. Being a refugee in a city, converge of a place in the city, being a part of myth of feeling himself as a citizen and soon rejecting the city life, and the dreams of being the other, living outside of the city, so on so forth. Which feeling must be the right to choose, to have to live a better life? Thus, the paper will be about the Happy City Workshop, which was held on Trabzon in 2014, during the architectural workshop series of Karadeniz Technical Universty and the short movie of the workshop that was shot in there by 15 students. The paper also will not only have all of those discussion about the relationship among the city, the capitalism, the neo-liberal economies and the architecture, but also it will discuss the utopias and dystopias related with the happy city and all who are searching of, living on, discuss and examine the city, who has an utopia of the city, or who see that all of the utopias of the city can be dystopias as well of others, and those who reject them all, while put a light to the written texts chronologically about the city from the first city focused written text of St.Augustin’s The City of God to Renzo Piano’s city discussions and Charles Mongomery’s book of Happy City. © The Turkish Online Journal of Educational Technology.
Keywords: Architecture; Historicism; Historicity; History; Past